(untitled) (Latin-American Journal of Computing, 2017)
There is a wide variety of statistical tools developed for making decisions in the business context. The analysis of functional data is a area of study of growing importance in the last years. In the present paper some of its applied techniques are proposed to make analysis of financial risk. Specifically, results from exploratory functional analysis, identification of atypical data and the construction of supervised classification models based on the risk classification of credit unions, subject to the control of the Superintendency of Banks of Ecuador, taking as functional variables the NPL ratio and the net profit margin in the period July 2011 to December 2012.